Algorithms and High-Frequency Trading in Financial Markets - Danzeng, Zhuoma; Gao, Hao; Guan, Ziqi (Transactions on Economics, Business and Management Research, 2024)
This paper examines the transformative impact of high-frequency trading (HFT) and algorithmic trading (AT) on financial markets. With the development of computer technology and the globalization of financial markets, HFT and AT have become the main trading methods in financial markets. The application of these technologies has not only changed the way trades are executed but has also significantly impacted market structure and participant behavior. FT utilizes ultra-fast algorithms and network technology to execute trades at high speeds and capture small price differences.AT automatically executes trades based on pre-determined strategies, which improves efficiency and reduces human error. Both approaches increase market liquidity and speed, raising challenges such as market manipulation and systemic risk. This study examines these trading mechanisms’ strategies, technological underpinnings, and market effects, emphasizing the need for strong regulatory frameworks to ensure fair and stable markets. The study also discusses the role of data visualization in analyzing trading activities and its limitations, highlighting the potential of advanced visualization techniques to improve market analysis.